HORROR ELEMENTS IN THE CARTOON MEDIA, THE STORYTELLING TECHNIQUE AND ATMOSPHERE CREATION TO STIMULATE THE AUDIENCE’S EMOTIONS - Promjeen, Wanwisa; Boonchuai, Poschanan (Journal of Social Science and Cultural, 2025)
This research article aims to study the guidelines and processes of creating a horror atmosphere from artistic elements. Create works from concepts and processes to the prototype of the knowledge of designing and creating a horror atmosphere from artistic elements. It is a quantitative research. Those who provide important information are experts in creating horror atmospheres, specifically selected, 15 men, 15 women, a total of 30 people, and classified by age range of not less than 18-29 years old, who have experience and understanding of storytelling and using cartoon media. The tools used in the research include in-depth interviews, collect data with in-depth interviews, analyze the data. The results of the research found that the guidelines and processes of creating a horror atmosphere from art elements in creating a horror atmosphere from ghost cartoons per book. In conclusion, the ghost cartoon is a Thai culture that can attract and create participation of people in society and be powerful with elements of lines, drawings, and stories related to everyday life. There is also immortality. Creation of works from ideas and processes to the prototype of design knowledge, creating a horror atmosphere from artistic elements. The objective is to create characters that are consistent with cultural codes related to religion, beliefs, values, views, aesthetics of design based on artistic elements. Because Thai cartoons today are also influenced by foreign countries, especially Japan and China, and when the social model enters the digital age, cartoons have changed beyond paper print media to online print media. Which has changed in content, access patterns and cultural integration Reflecting the changes in Thai society very well.